Targeted Next-Generation Sequencing of Cancer-Related Genes in a Norwegian Patient Cohort With Head and Neck Squamous Cell Carcinoma Reveals Novel Actionable Mutations and Correlations With Pathological Parameters - Dongre, Harsh N.; Haave, Hilde; Fromreide, Siren; Erland, Fredrik A.; Moe, Svein Erik Emblem; Dhayalan, Sophia Manueldas; Riis, Rasmus Kopperud; Sapkota, Dipak; Costea, Daniela Elena; Aarstad, Hans Jorgen; Vintermyr, Olav K. (Frontiers in Oncology, 2021)
Background Targeted next-generation sequencing (NGS) is increasingly applied in clinical oncology to advance personalized treatment. Despite success in many other tumour types, use of targeted NGS panels for assisting diagnosis and treatment of head and neck squamous cell carcinomas (HNSCC) is still limited. Aim The focus of this study was to establish a robust NGS panel targeting most frequent cancer mutations in long-term preserved formalin-fixed paraffin-embedded (FFPE) tissue samples of HNSCC from routine diagnostics. Materials and Methods Tumour DNA obtained from archival FFPE tissue blocks of HNSCC patients treated at Haukeland University Hospital between 2003-2016 (n=111) was subjected to mutational analysis using a custom made AmpliSeq Library PLUS panel targeting 31 genes (Illumina). Associations between mutational burden and clinical and pathological parameters were investigated. Mutation and corresponding clinicopathological data from HNSCC were extracted for selected genes from the Cancer Genome Atlas (TCGA) and used for Chi-square and Kaplan-Meier analysis. Results The threshold for sufficient number of reads was attained in 104 (93.7%) cases. Although the specific number of PCR amplified reads detected decreased, the number of NGS-annotated mutations did not significantly change with increased tissue preservation time. In HPV-negative carcinomas, mutations were detected mainly in TP53 (73.3%), FAT1 (26.7%) and FLG (16.7%) whereas in HPV-positive, the common mutations were in FLG (24.3%) FAT1 (17%) and FGFR3 (14.6%) genes. Other less common pathogenic mutations, including well reported SNPs were reproducibly identified. Presence of at least one cancer-specific mutations was found to be positively associated with an extensive desmoplastic stroma (p=0.019), and an aggressive type of invasive front (p=0.035), and negatively associated with the degree of differentiation (p=0.041). Analysis of TCGA data corroborated the association between cancer-specific mutations and tumour differentiation and survival analysis showed that tumours with at least one mutation had shorter disease-free and overall survival (p=0.005). Conclusions A custom made targeted NGS panel could reliably detect several specific mutations in archival samples of HNSCCs preserved up to 17 years. Using this method novel associations between mutational burden and clinical and pathological parameters were detected and actionable mutations in HPV-positive HNSCC were discovered.